Answer:
Step-by-step explanation:
We will subtract the amount of water that leaked out from the amount of water originally in the fish tank.
![\displaystyle \frac{3}{4} - \frac{1}{3} =\frac{3*3}{4*3} -\frac{1*4}{3*4} =\frac{9}{12} -\frac{4}{12}=\frac{5}{12}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cfrac%7B3%7D%7B4%7D%20-%20%5Cfrac%7B1%7D%7B3%7D%20%3D%5Cfrac%7B3%2A3%7D%7B4%2A3%7D%20-%5Cfrac%7B1%2A4%7D%7B3%2A4%7D%20%3D%5Cfrac%7B9%7D%7B12%7D%20-%5Cfrac%7B4%7D%7B12%7D%3D%5Cfrac%7B5%7D%7B12%7D)
The fish tank is
of the way full.
Answer:
2438.4
Step-by-step explanation:
multiply 96 by 25.4
Answer:
x = 27
Step-by-step explanation:
AC // DE
m∠ABD ≅ m∠BDE = 72°
m∠ADB + m∠BDE + m∠EDF = 180°
2x + 72° + 2x = 180°
4x = 108°
x = 27°